Discovering the value of tamaulipecans magueys - Treviño-Carreón, Jacinto (Universidad Autónoma de Tamaulipas, 2011)
It presents information on the knowledge of maguey from the ecological point of view and its use by local communities with an emphasis in Tamaulipas. The information was obtained from literature sources, review of plant collections, interviews and field verification.